Effects of stimulus repetition rates on the auditory brainstem response to level-specific CE-Chirp in normal-hearing adults - Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Jamal, Fatin Nabilah; Marzuki, Muhammad Nasrullah; Mazlan, Mohd Naufal Shah (American Speech and Hearing Association (ASHA), 2020)
Purpose The purpose of this study is to investigate the influence of stimulus repetition rates on the auditory brainstem response (ABR) to Level-Specific (LS) CE-Chirp and click stimuli at multiple intensity levels in normal-hearing adults.